Vitiligo and Mental Health: Natural Compounds' Usefulness - Luca Di Bartolomeo; Paolo Custurone; Natasha Irrera; Francesco Borgia; Federico Vaccaro; Francesco Squadrito; Mario Vaccaro (MDPI AG, 2023)
Vitiligo is an autoimmune dermatosis frequently associated with other comorbidities, such as mental health disorders. It is unclear if vitiligo triggers mental disorders or if mental disorders trigger vitiligo, but each one affects and worsen the other, if present at the same time. Both mental health disorders and vitiligo present a multifactorial pathogenesis and often require prolonged periods of therapy, sometimes with poor results. Given the possible link of common pathogenetic factors and the need of integrated therapies, the aim of this review is to look at natural compounds as possible supplements for both conditions. The results yielded show a possible role of these supplements in ameliorating both conditions, thus helping these patients to achieve a better quality of life and reduce the need for prolonged therapies. The limitations regarding the relative lack of in vivo studies, and the increasing need to lighten the burden of these chronic diseases, suggests that it is mandatory to proceed with further trials.